Did injury incidence in alpine ski racing change after equipment regulations? An evaluation based on the injury surveillance system of the Austrian Ski Federation. Issue 10 (October 2021) - Platzer, Hans-Peter; Barth, Michael; Giger, Anton; Schröcksnadel, Peter; Nachbauer, Werner
Abstract: Objectives: To assess the effects of alpine competition equipment regulations from 2003, 2007 and 2012 on severe injury incidence. Design: Case study Method: Data originated from records of the injury surveillance system of the Austrian Ski Federation. Injuries from the seasons 2001–2017 were divided in four periods between the equipment regulations. For comparison of consecutive periods, risk ratios (RR = later period / preceding period) with 95% CI were calculated. Total severe injury events, events with severe knee injuries, and events with severe ACL injuries were separately investigated. Results: A significant increase of total severe injury incidence was found after the equipment regulation in 2003 (RR 1.52, 95% CI 1.00–2.31). None of the other comparisons revealed significance (p < 0.05) or statistical trends (p < 0.1). Only the minority (40%) of the RR showed a reduction in the injury incidence of the Austrian Ski Team (lowest RR 0.78). 60% of the RR increased after the regulations (highest RR 1.63). Conclusions: Even though statistical uncertainties remain, our findings allow the conclusion, that the implemented equipment regulations did not cause a noticeable reduction of injuries. The three analysed equipment regulations were not appropriate or were counteracted by other factors.